A moisture and heat resistant flame-retardant polyether ether ketone modified material and a preparation method thereof
Patent Information
- Application Number
- CN202610216789.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-14
- Publication Date
- 2026-09-22
- Estimated Expiration
- 2046-02-14
AI Technical Summary
本发明通过交联杂化改性与界面协同调控,能够有效解决传统阻燃剂耐温性差及易诱发基体水解的缺陷,并在高温高湿老化后仍保持极高的力学强度,从而显著提升了材料的耐湿热稳定性和综合服役性能
1.耐湿热老化稳定性更优:本发明通过POSS笼型结构的立体位阻效应构建疏水屏障,有效抑制了磷氮阻燃剂在高温高湿环境下的水解产酸行为,阻断了引发基体降解的自催化过程。相较于现有技术,该材料在湿热老化后的力学强度保持率处于更高水平,显著提升了恶劣工况下的服役可靠性。
Smart Images

Figure CN121930651B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer material modification technology, specifically to a moisture-heat resistant and flame-retardant polyether ether ketone modified material and its preparation method. Background Technology
[0002] Polyetheretherketone (PEEK), a top-tier specialty engineering plastic, holds a vital position in aerospace, electronics, and high-end automotive manufacturing due to its excellent mechanical properties, chemical resistance, and thermal stability. As modern industry places increasingly stringent demands on material service environments, particularly under extreme conditions such as high temperature and humidity, the comprehensive performance of materials faces greater challenges. While PEEK itself possesses certain flame retardancy, in applications requiring thin-walled components or extremely high fire resistance ratings, relying solely on the base resin often fails to meet stringent flame retardancy standards, typically necessitating modification with flame retardants.
[0003] Existing modification technologies face numerous bottlenecks in practical applications. Due to the extremely high processing temperature of PEEK, conventional flame retardants are prone to thermal decomposition during high-temperature melt blending. This not only leads to a decrease in flame retardant efficiency but also causes porosity within the material due to decomposition products, severely weakening the mechanical strength and appearance quality of the manufactured parts. Simultaneously, many traditional flame retardants have poor compatibility with the PEEK matrix and are either highly hydrophilic or unstable in humid and hot environments. When materials are exposed to high temperature and humidity environments for extended periods, these additives can easily induce interfacial defects or accelerate the hydrolytic aging of the matrix resin, resulting in a sharp decline in the material's mechanical properties, i.e., insufficient resistance to humid and hot aging. How to achieve a synergistic improvement in the excellent flame retardancy and long-term resistance to humid and hot aging of PEEK materials without sacrificing processing fluidity and mechanical strength is a pressing technical challenge that needs to be overcome in this field. Summary of the Invention
[0004] The purpose of this invention is to address the problems existing in the prior art by providing a moisture-heat resistant, flame-retardant polyether ether ketone (PEEK) modified material and its preparation method. This invention, through cross-linking hybrid modification and interfacial synergistic regulation, effectively solves the defects of traditional flame retardants, such as poor temperature resistance and susceptibility to matrix hydrolysis. Furthermore, it maintains extremely high mechanical strength even after high-temperature and high-humidity aging, thereby significantly improving the material's moisture-heat resistance and overall service performance.
[0005] To achieve the above objectives, the technical solution adopted by this invention is: a moisture-heat resistant flame-retardant polyether ether ketone modified material and its preparation method, which is prepared from the following raw materials in parts by weight through a melt blending extrusion process: polyether ether ketone: 70-90 parts; polyphenylene sulfide: 5-15 parts; self-crosslinking modified phosphorus-nitrogen flame retardant: 10-25 parts; hydrolysis-resistant stabilizer: 0.5-2.0 parts; antioxidant: 0.1-0.8 parts; lubricating dispersant: 0.2-1.0 parts; The preparation method of the self-crosslinking modified phosphorus-nitrogen flame retardant is as follows: S1. Dissolve hexachlorocyclotriphosphazene in dry tetrahydrofuran solvent. Under nitrogen protection at 0-5℃, add 1-3% (by weight) of deionized water (an equal volume of anhydrous ethanol can be used as a co-solvent) to vinyltrimethoxysilane for pre-hydrolysis for 30-60 minutes. Then, slowly add the pre-hydrolyzed vinyltrimethoxysilane to the above system, and add triethylamine to convert the generated vinylsilanol into a silanolate. The silanolate undergoes nucleophilic substitution of the P-Cl bond to form a PO-Si bond, and the byproduct HCl is neutralized by triethylamine acid. The mass ratio of hexachlorocyclotriphosphazene to vinyltrimethoxysilane is 1:1.2-1.5, and the mass of triethylamine added is 0.8-1.0 times the mass of vinyltrimethoxysilane. After the addition is complete, heat to 40-50℃ and react for 4-6 hours. S2. After the reaction system cools to room temperature, add a hydroxyl-containing cage-like silsesquioxane, the mass of which is 2.0-2.5 times the mass of hexachlorocyclotriphosphazene, and reflux at 65-75℃ for 8-12 hours. S3. After the reaction is complete, the solvent is removed by rotary evaporation. The product is washed with deionized water 3-5 times and dried in a vacuum oven at 80-100℃ to constant weight to obtain a self-crosslinking modified phosphorus-nitrogen flame retardant.
[0006] Further, the hydroxyl-containing cage-like silsesquioxane is octa{4-[(2-{[(dimethylsilyl)oxy]methyl}phenyl)ethyl]phenyl}methyl-1,3,5,7,9,11,13,15-octa(hydroxymethyl)-2,4,6,8,10,12,14,16,17,18,19,20-dodecano-1,3,5,7,9,11,13,15-octasilpentane[9.5.1.1]]. 3 , 9 .1 5 , 15 .1 7 , 13 Eicosane, whose chemical structure is shown in Formula 1: Formula 1: ; Further, the octa{4-[(2-{[(dimethylsilyl)oxy]methyl}phenyl)ethyl]phenyl}methyl-1,3,5,7,9,11,13,15-octa(hydroxymethyl)-2,4,6,8,10,12,14,16,17,18,19,20-dodecano-1,3,5,7,9,11,13,15-octasilpentane[9.5.1.1]] is a methyl-4- ... 3 , 9 .1 5 , 15 .1 7 , 13Preparation method of eicosane: ; Raw materials 1 and 2 were synthesized via a hydrosilylation reaction to obtain octa{4-[(2-{[(dimethylsilyl)oxy]methyl}phenyl)ethyl]phenyl}methyl-1,3,5,7,9,11,13,15-octa(hydroxymethyl)-2,4,6,8,10,12,14,16,17,18,19,20-dodecano-1,3,5,7,9,11,13,15-octasilpentane[9.5.1.1]. 3 , 9 .1 5 , 15 .1 7 , 13 Eicosane.
[0007] Furthermore, the hydrolysis-resistant stabilizer is selected from polycarbodiimide or bisoxazoline compounds.
[0008] Furthermore, the antioxidant is a mixture of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris(2,4-di-tert-butylphenyl)phosphite, with a mass ratio of 1:1-2.
[0009] Furthermore, the lubricating dispersant is one of montan wax, polytetrafluoroethylene micro powder, or calcium stearate.
[0010] Furthermore, the pre-modification mechanism of the vinyltrimethoxysilane is as follows: in the presence of triethylamine, vinyltrimethoxysilane undergoes controlled hydrolysis with trace amounts of water to generate vinylsilanol / silanolate, whose O - As a nucleophile, it replaces the P-Cl bond on hexachlorocyclotriphosphazene to form a PO-Si bond. The generated HCl is captured by triethylamine, thereby introducing a siloxane group that can be subsequently condensed onto the phosphorus-nitrogen skeleton.
[0011] Furthermore, the mechanism of action of the self-crosslinking modified phosphorus-nitrogen flame retardant is as follows: using hexachlorocyclotriphosphazene as a high-phosphorus-nitrogen content flame-retardant skeleton, pre-modified with vinyltrimethoxysilane to introduce reactive siloxane groups into the molecular chain; subsequently, octa{4-[(2-{[(dimethylsilyl)oxy]methyl}phenyl)ethyl]phenyl}methyl-1,3,5,7,9,11,13,15-octa(hydroxymethyl)-2,4,6,8,10,12,14,16,17,18,19,20-dodecano-1,3,5,7,9,11,13,15-octasilpentane[9.5.1.1] is introduced. 3 , 9 .1 5 , 15 .1 7 , 13Eicosane, utilizing the abundant benzyl alcohol hydroxyl groups on the periphery of the POSS molecule, undergoes a condensation grafting reaction with the aforementioned siloxane groups or phosphorus-nitrogen skeleton, thereby constructing a three-dimensional network cross-linked structure with a "cage-like core-flexible arm-phosphorus-nitrogen skeleton". This structure, on the one hand, leverages the significant steric hindrance effect of POSS and the hydrophobic properties of the siloxane segments to effectively shield the internal chemical bonds, significantly delaying the penetration and erosion of water molecules under high temperature and humidity conditions, and inhibiting the degradation of the polyether ether ketone matrix caused by the hydrolysis of phosphorus-nitrogen bonds. On the other hand, during material combustion, the decomposition of phosphorus and nitrogen elements generates free radical scavengers that interrupt the chain reaction. Simultaneously, the POSS cage structure transforms in situ at high temperatures into a highly thermally stable silica ceramic skeleton, promoting the dehydration and char formation of the polymer matrix and enhancing the density and adhesion of the char layer, forming a robust "phosphorus-nitrogen-silicon" synergistic composite barrier layer. This effectively isolates heat transfer and oxygen diffusion, ultimately endowing the material with excellent resistance to damp heat aging while achieving high-efficiency flame retardancy.
[0012] A method for preparing a moisture-heat resistant and flame-retardant modified polyetheretherketone material includes the following steps: (1) Raw material pretreatment: Polyether ether ketone and polyphenylene sulfide are placed in a forced-air drying oven for high-temperature dehumidification treatment until the moisture content is less than 0.05%; (2) High-speed mixing: The dried polyether ether ketone and polyphenylene sulfide, along with the self-crosslinking modified phosphorus and nitrogen flame retardant, hydrolysis-resistant stabilizer, antioxidant and lubricating dispersant, are put into a high-speed mixer and stirred until the material temperature rises to 110-130℃, then discharged and cooled. (3) Melt extrusion: The mixture is fed into a twin-screw extruder, and after shearing, melting and homogenization, it is extruded; (4) Post-processing: The extruded strips are cooled, dried, granulated and dried to obtain modified material particles.
[0013] Furthermore, the high-temperature dehumidification treatment in step (1) is at a temperature of 120-150℃ and a treatment time of 4-8 hours.
[0014] A method for preparing a moisture-heat resistant and flame-retardant polyether ether ketone modified material, characterized in that the temperature of each zone of the twin-screw extruder in step (3) is set as follows: feeding zone 280-310℃, melting zone 330-360℃, homogenization zone 340-370℃, and die head 330-350℃; the screw speed is controlled at 200-500 rpm.
[0015] Furthermore, in step (3), the screw assembly of the twin-screw extruder includes at least three sets of kneading block elements, and the vacuum degree of the vacuum exhaust section is controlled between -0.08MPa and -0.1MPa.
[0016] Application of a moisture-heat resistant and flame-retardant modified polyether ether ketone material in aerospace, electronics, or high-end automobile manufacturing.
[0017] The moisture-heat resistant and flame-retardant polyether ether ketone modified material of this invention achieves a dual improvement in mechanical property retention and flame-retardant performance under high temperature and high humidity environments through the molecular structure design and interfacial synergistic effect of the components. The core mechanism lies in the construction of a self-crosslinking modified phosphorus-nitrogen flame retardant, which utilizes octa{4-[(2-{[(dimethylsilyl)oxy]methyl}phenyl)ethyl]phenyl}methyl-1,3,5,7,9,11,13,15-octa(hydroxymethyl)-2,4,6,8,10,12,14,16,17,18,19,20-dodecano-1,3,5,7,9,11,13,15-octasilpentane[9.5.1.1] 3 , 9 .1 5 , 15 .1 7 , 13 The cage-like topology and multifunctional characteristics of eicosane enabled stereochemical modification of the hexachlorocyclotriphosphazene (PCS) backbone. The benzyl alcohol hydroxyl groups on the periphery of the PCS underwent graft condensation with the phosphorus-nitrogen backbone activated by a silane coupling agent, forming a highly cross-linked organic-inorganic hybrid network. This large cage-like structure produced a significant steric hindrance effect, acting like a hydrophobic and dense molecular "shield" around the hydrolysis-sensitive PN bonds. This effectively blocked the penetration and attack of water molecules in humid and hot environments, and effectively inhibited the autocatalytic process that leads to the release of acidic substances from the flame retardant, thereby inducing the degradation of the polyetheretherketone (PEEK) matrix.
[0018] This hybrid flame retardant also possesses an extremely high thermal decomposition temperature, enabling it to withstand the high shear heat during the melting and processing of polyether ether ketone (PEEK) without degradation, thus avoiding the microporous defects inside the parts caused by the decomposition and foaming of traditional flame retardants. When the material encounters a fire, the phosphorus and nitrogen elements decompose under heat, causing the polymer matrix to dehydrate and char. Meanwhile, the POSS cage transforms in situ into a silica ceramic framework with excellent thermal stability at high temperatures. This synergistic effect of "ceramization-carbonization" generates a dense and robust composite carbon layer structure that effectively isolates oxygen and heat transfer. Furthermore, the polyphenylene sulfide (PPS) introduced into the system fills the spaces between PEEK molecular chains with its high fluidity, improving processing rheology. Combined with the chemical capture effect of hydrolysis-resistant stabilizers (such as polycarbodiimide) on residual terminal carboxyl groups in the system, it further repairs microcracks or chain breaks that may occur due to aging, thereby ensuring that the modified material maintains excellent mechanical strength and flame retardant integrity even after long-term humid heat aging.
[0019] Compared with the prior art, the beneficial effects of the present invention are: 1. Superior Stability in Moist and Heat Aging: This invention utilizes the steric hindrance effect of the POSS cage structure to create a hydrophobic barrier, effectively inhibiting the hydrolysis and acid production of phosphorus and nitrogen flame retardants under high temperature and humidity conditions, and blocking the autocatalytic process that triggers matrix degradation. Compared to existing technologies, this material maintains a higher level of mechanical strength retention after moist and heat aging, significantly improving its service reliability under harsh conditions.
[0020] 2. Enhanced processing thermal stability and flame retardant efficiency: The hybrid flame retardant used in this modified material exhibits excellent temperature resistance, enabling it to withstand the high-temperature melting process of polyetheretherketone (PEEK) without easily decomposing and generating pores, thus improving the density of the manufactured parts. During combustion, the induced "ceramization-carbonization" composite layer structure is more robust, effectively isolating heat and oxygen transfer and achieving excellent vertical combustion rating even with low addition levels.
[0021] 3. Improved interfacial compatibility and overall mechanical properties: By introducing high-flowability resin and hydrolysis-resistant stabilizer for synergistic regulation, the interfacial bonding between the matrix and the highly filled flame retardant is improved, and microscopic defects that may occur due to aging are repaired. Compared with traditional modified materials, this invention imparts high flame retardancy to the material while maintaining high tensile strength and impact toughness, and also takes into account processing rheology. Attached Figure Description
[0022] Figure 1 The octa{4-[(2-{[(dimethylsilyl)oxy]methyl}phenyl)ethyl]phenyl}methyl-1,3,5,7,9,11,13,15-octa(hydroxymethyl)-2,4,6,8,10,12,14,16,17,18,19,20-dodecano-1,3,5,7,9,11,13,15-octasilpentane[9.5.1.1]] described in this invention is... 3 , 9 .1 5 , 15 .1 7 , 13 Infrared spectrum of eicosane.
[0023] Figure 2 This is the infrared spectrum of the self-crosslinking modified phosphorus-nitrogen flame retardant described in this invention. Detailed Implementation
[0024] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are merely some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] Preparation Example 1 octa{4-[(2-{[(dimethylsilyl)oxy]methyl}phenyl)ethyl]phenyl}methyl-1,3,5,7,9,11,13,15-octa(hydroxymethyl)-2,4,6,8,10,12,14,16,17,18,19,20-dodecano-1,3,5,7,9,11,13,15-octasilpentane[9.5.1.1] 3 , 9 .1 5 , 15 .1 7 , 13 Preparation of eicosane: ; Under a nitrogen atmosphere, 1.0 g of raw material 1, 0.96 g of raw material 2, and 20 mL of anhydrous toluene were added sequentially to the reaction system, followed by 20 μL of Karstedt platinum catalyst solution. The mixture was then heated to 90°C and refluxed with stirring for 24 hours. After the reaction was completed, the mixture was cooled to room temperature, and 0.5 g of activated carbon powder was added and stirred for 40 minutes. The mixture was then filtered with diatomaceous earth assistance, and the filter cake was washed with 5 mL of toluene. The filtrates were combined and concentrated by rotary evaporation to approximately 4 mL. The concentrate was then slowly added dropwise to 100 mL of vigorously stirred cold diethyl ether / n-hexane. The solid was precipitated in a 1:3 (volume ratio) mixed solution, centrifuged to collect the bottom solid, and dried in a vacuum drying oven at 45°C for 24 hours to obtain 1.76 g of octa{4-[(2-{[(dimethylsilyl)oxy]methyl}phenyl)ethyl]phenyl}methyl-1,3,5,7,9,11,13,15-octa(hydroxymethyl)-2,4,6,8,10,12,14,16,17,18,19,20-dodecano-1,3,5,7,9,11,13,15-octasilpentane[9.5.1.1]]. 3 , 9 .1 5 , 115 .1 7 , 13 Eicosane, its infrared spectrum is as follows: Figure 1 As shown.
[0026] Structural assessment: octa{4-[(2-{[(dimethylsilyl)oxy]methyl}phenyl)ethyl]phenyl}methyl-1,3,5,7,9,11,13,15-octa(hydroxymethyl)-2,4,6,8,10,12,14,16,17,18,19,20-dodecano-1,3,5,7,9,11,13,15-octasylsilanepentane[9.5.1.13,9.15, 1 [15.17,13] Mass spectrometry (MS) of eicosane [M+Na] + :2095; octa{4-[(2-{[(dimethylsilyl)oxy]methyl}phenyl)ethyl]phenyl}methyl-1,3,5,7,9,11,13,15-octa(hydroxymethyl)-2,4,6,8,10,12,14,16,17,18,19,20-dodecano-1,3,5,7,9,11,13,15-octasylsilanepentane[9.5.1.13,9.15, 1 [15.17,13] NMR of eicosane: 1 HNMR-DMSO-d6): δ7.52(d,16H),7.30(d,16H),7.15(d,8H),6.45(d,8H),5.18(t,8H,),4.50(d,16H),0.25(s,48H).
[0027] Preparation Example 2 Preparation of self-crosslinking modified phosphorus-nitrogen flame retardants: S1. Preparation of intermediates: 10.0 g of hexachlorocyclotriphosphazene was dissolved in 120 mL of dry tetrahydrofuran solvent and placed in a reaction vessel. Under nitrogen protection at 0 °C, 13.0 g of vinyltrimethoxysilane was mixed with 2% (w / w) of deionized water for pre-hydrolysis for 45 minutes, and then slowly added dropwise to the reaction vessel, while 11.7 g of triethylamine was added dropwise simultaneously to convert the generated vinylsilanol into a silanolate. The silanolate underwent nucleophilic substitution of the P-Cl bond to form a PO-Si bond, and the byproduct HCl was neutralized by triethylamine. After the addition was complete, the reaction system was heated to 45 °C and reacted at this temperature for 5 hours.
[0028] S2. Grafting and crosslinking reaction: After the above reaction system has cooled naturally to room temperature, 22.0 g of octa{4-[(2-{[(dimethylsilyl)oxy]methyl}phenyl)ethyl]phenyl}methyl-1,3,5,7,9,11,13,15-octa(hydroxymethyl)-2,4,6,8,10,12,14,16,17,18,19,20-dodecano-1,3,5,7,9,11,13,15-octasilpentane[9.5.1.1] obtained in Preparation Example 1 was added to the system. 3 , 9 .1 5 , 115 .1 7 , 13 [Eicosane. The system was then heated to 70°C and refluxed for 10 hours.]
[0029] S3. Post-processing and purification: After the reaction, the solvent was removed by rotary evaporation. The obtained product was washed four times with deionized water to remove reaction byproducts and residual impurities. Finally, the washed product was dried in a vacuum oven at 90°C to constant weight to obtain a light yellow powdery self-crosslinking modified phosphorus-nitrogen flame retardant, the infrared spectrum of which is shown below. Figure 2 As shown.
[0030] Comparative Preparation Example 1 Preparation of self-crosslinking modified phosphorus-nitrogen flame retardants Referring to the preparation method of Preparation Example 2, the octa{4-[(2-{[(dimethylsilyl)oxy]methyl}phenyl)ethyl]phenyl}methyl-1,3,5,7,9,11,13,15-octa(hydroxymethyl)-2,4,6,8,10,12,14,16,17,18,19,20-dodecano-1,3,5,7,9,11,13,15-octasilpentane[9.5.1.1]] was prepared. 3 , 9 .1 5 , 115 .1 7 , 13 [Replace eicosane with] The rest remains the same as in Preparation Example 2.
[0031] Comparative Preparation Example 2 Preparation of self-crosslinking modified phosphorus-nitrogen flame retardants Referring to the preparation method of Preparation Example 2, the octa{4-[(2-{[(dimethylsilyl)oxy]methyl}phenyl)ethyl]phenyl}methyl-1,3,5,7,9,11,13,15-octa(hydroxymethyl)-2,4,6,8,10,12,14,16,17,18,19,20-dodecano-1,3,5,7,9,11,13,15-octasilpentane[9.5.1.1]] was prepared. 3 , 9 .1 5 , 115 .1 7 , 13 [Replace eicosane with] The rest remains the same as in Preparation Example 2.
[0032] Example 1 Preparation of a moisture-heat resistant and flame-retardant modified polyetheretherketone material: 1. Raw material components by weight: Polyetheretherketone (PEEK): 80 parts, purchased from Shanghai Mairui Biochemical Technology Co., Ltd., CAS: 29658-26-2; Polyphenylene sulfide: 10 parts, purchased from Shanghai Yuanye Biotechnology Co., Ltd., CAS No.: 25212-74-2; Self-crosslinking modified phosphorus-nitrogen flame retardant: 18 parts (using the self-crosslinking modified phosphorus-nitrogen flame retardant prepared in Preparation Example 1 above); Hydrolysis-resistant stabilizer: 1.2 parts (polycarbodiimide is preferred); Antioxidant: 0.5 parts (a mixture of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris(2,4-di-tert-butylphenyl)phosphite in a mass ratio of 1:1.5); Lubricating dispersant: 0.6 parts (Montan wax is selected).
[0033] 2. Preparation method: (1) Deep drying of raw materials: Polyether ether ketone and polyphenylene sulfide are placed in a forced-air drying oven, the temperature is set at 140℃, and high-temperature dehumidification treatment is carried out for 6 hours. The moisture content is tested and reduced to 0.03% (meeting the requirement of less than 0.05%), so as to eliminate the influence of moisture on high-temperature processing.
[0034] (2) High-speed dispersion and mixing: The dried polyether ether ketone and polyphenylene sulfide, along with the self-crosslinking modified phosphorus nitrogen flame retardant, polycarbodiimide, antioxidant and montan wax, are put into a high-speed mixer. The equipment is started and stirred at high speed. The temperature of the material is gradually increased by frictional heat. When the material temperature reaches 120°C, stirring is stopped, the material is discharged and cooled to room temperature to obtain the premix.
[0035] (3) Reactive melt extrusion: The premixed material is added to the main feed port of a twin-screw extruder. Four sets of kneading block elements are installed in the extruder screw assembly to enhance the shear dispersion effect. The temperatures of each zone are set as follows: feeding section 290℃, melting section 345℃, homogenization section 360℃, and die head 340℃; the screw speed is set to 350 rpm. At the same time, a vacuum of -0.09 MPa is maintained in the vacuum exhaust section to extract small molecule volatiles.
[0036] (4) Granulation and post-processing: The extruded melt strip is cooled and shaped in a water bath, the surface moisture is dried by an air knife, and it is then cut into uniform particles by a pelletizer. Finally, it is dried at 120°C for 3 hours to obtain moisture-resistant and flame-retardant polyether ether ketone modified material particles.
[0037] Example 2 Preparation of a moisture-heat resistant and flame-retardant modified polyetheretherketone material: 1. Raw material components by weight: Polyetheretherketone: 90 parts; Polyphenylene sulfide: 5 parts; Self-crosslinking modified phosphorus-nitrogen flame retardant: 10 parts (using the self-crosslinking modified phosphorus-nitrogen flame retardant prepared in Preparation Example 1 above); Hydrolysis-resistant stabilizer: 0.5 parts (polycarbodiimide is preferred); Antioxidant: 0.1 parts (a mixture of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris(2,4-di-tert-butylphenyl)phosphite in a mass ratio of 1:1); Lubricating dispersant: 0.2 parts (using polytetrafluoroethylene micro powder).
[0038] 2. Preparation method: Refer to the preparation method of Example 1, wherein the high temperature dehumidification temperature in step (1) is set to 120℃ and the time is 8 hours; in step (3), the extruder feeding section is 280℃, the melting section is 330℃, the homogenization section is 340℃, the die head is 330℃, the screw speed is 200rpm, and the vacuum degree is -0.08MPa.
[0039] Example 3 Preparation of a moisture-heat resistant and flame-retardant modified polyetheretherketone material: 1. Raw material components by weight: Polyetheretherketone: 70 parts; Polyphenylene sulfide: 15 parts; Self-crosslinking modified phosphorus-nitrogen flame retardant: 25 parts (using the self-crosslinking modified phosphorus-nitrogen flame retardant prepared in Preparation Example 1 above); Hydrolysis-resistant stabilizer: 2.0 parts (polycarbodiimide is selected); Antioxidant: 0.8 parts (a mixture of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris(2,4-di-tert-butylphenyl)phosphite in a mass ratio of 1:2); Lubricating dispersant: 1.0 part (calcium stearate is selected).
[0040] 2. Preparation method: Refer to the preparation method of Example 1, wherein the high temperature dehumidification temperature in step (1) is set to 150℃ and the time is 4 hours; in step (3), the extruder feeding section is 310℃, the melting section is 360℃, the homogenization section is 370℃, the die head is 350℃, the screw speed is 500rpm, and the vacuum degree is -0.1MPa.
[0041] Comparative Example 1 The preparation of a moisture-heat resistant flame-retardant polyether ether ketone modified material is carried out by referring to the preparation method of Example 1, except that the self-crosslinking modified phosphorus-nitrogen flame retardant is replaced with the self-crosslinking modified phosphorus-nitrogen flame retardant prepared in Comparative Preparation Example 1, and the rest is the same as in Example 1.
[0042] Comparative Example 2 The preparation of a moisture-heat resistant flame-retardant polyether ether ketone modified material is carried out by referring to the preparation method of Example 1, except that the self-crosslinking modified phosphorus-nitrogen flame retardant is replaced with the self-crosslinking modified phosphorus-nitrogen flame retardant prepared in Comparative Preparation Example 2, and the rest is the same as in Example 1.
[0043] Performance testing: 1. Retention rate of mechanical properties (tensile strength retention rate) after resistant to damp heat aging: According to the damp heat aging conditions in GB / T7141-2008 "Plastics Thermal Aging Test Method" and GB / T1040.1-2006 "Determination of Tensile Properties of Plastics Part 1: General Rules", I-shaped dumbbell-shaped tensile specimens (size: total length 150mm, effective gauge length 50mm, thickness 4mm) were prepared by injection molding using the target modified material. Ten specimens were prepared in each group (5 for pre-aging test and 5 for post-aging test). The specimens were dried at 120℃ for 4h to remove residual moisture from the processing and cooled to room temperature for later use. The damp heat aging conditions were set at a temperature of 85℃ and a relative humidity of 85%RH, with an aging time of 1000h (meeting the long-term service requirements of aerospace and electronics fields). The tensile test conditions were a tensile speed of 5mm / min, an ambient temperature of 23℃ and a relative humidity of 50%RH, and were conducted using an electronic universal testing machine. During the test, five unaged specimens were first tested for tensile strength according to the standard and the average value was recorded. The remaining five specimens were aged for 1000 hours under set conditions, then balanced in a 23℃ / 50%RH environment for 24 hours and the tensile test was repeated and the average value was recorded. Finally, the tensile strength retention rate was calculated according to the formula η=(σ1 / σ0)×100%, and η≥85% was considered qualified. The data are shown in Table 1.
[0044] 2. Flame retardant properties (vertical burning rating): According to GB / T2408-2021 "Determination of Burning Performance of Plastics - Horizontal and Vertical Burning Methods", injection-molded vertical burning test strips (size: 127mm×12.7mm×3.2mm, key thickness, covering thin-walled parts) were prepared. Five test strips were prepared for each group. The test strips were dried at 80℃ for 2 hours to remove moisture before use. The test environment was 23℃ and 50%RH relative humidity. The ignition source was a methane flame (flame height 20mm), and a two-stage ignition method was used (each ignition lasted 10s, with the interval time as required by the standard). During testing, the sample was vertically fixed on the fixture, with its lower end 300mm away from the absorbent cotton (to receive drips). After the first ignition, the flame was removed and the self-extinguishing time (t1) was recorded (if it did not self-extinguish within 1 minute, the burning time was recorded and the test was terminated). After the sample flame extinguished, it was immediately ignited for 10 seconds. After the flame was removed, the self-extinguishing time (t2) was recorded. At the same time, it was observed whether the sample dripped and whether the drips ignited the absorbent cotton. According to the UL94 standard, the target level is V0 (meeting the flame retardant requirements of high-end fields) based on the following criteria: the sum of the two self-extinguishing times (t1+t2) ≤ 50s (3.2mm thickness), no drips igniting the absorbent cotton, and the burning length of the sample ≤ 50mm. The data is shown in Table 1.
[0045] 3. Mechanical strength at room temperature (tensile strength + cantilever beam impact strength): According to GB / T1040.1-2006 "Determination of tensile properties of plastics - Part 1: General rules" and GB / T1843-2008 "Determination of cantilever beam impact strength of plastics", the tensile specimens used were the same type I dumbbell specimens (5 specimens / set) as those used in the damp heat aging test. The impact specimens were unnotched cantilever beam specimens (size: 80mm×10mm×4mm, 5 specimens / set). All specimens were dried at 120℃ for 4 hours and cooled to room temperature before use. The tensile test conditions were a tensile speed of 5mm / min and an ambient temperature of 23℃ / 50%RH. The impact test conditions were an impact energy of 2.75J (unnotched), an ambient temperature of 23℃ / 50%RH, and a pendulum impact speed of 3.8m / s. During testing, tensile strength was measured on tensile specimens and impact absorption energy was measured on impact specimens according to the corresponding standards. The average value of five specimens was taken for each test (tensile strength unit: MPa, impact strength unit: kJ / m). 2 The results must meet the following requirements: tensile strength ≥ 90 MPa (reflecting the basic bearing capacity of the material), and unnotched impact strength of the cantilever beam ≥ 60 kJ / m. 2 (To ensure the material's impact resistance and reliability), the data is shown in Table 1.
[0046] Table 1 From the perspective of mechanical property retention rate after humid heat aging, the example group and the comparative group showed drastically different trends. After long-term high temperature and high humidity treatment, the tensile strength of the comparative group showed a significant cliff-like drop, indicating that severe degradation occurred inside the material; while all example groups showed only a very slight decrease in mechanical properties after aging, and the retention rate remained at a very high level, fully meeting the requirements for use under harsh working conditions.
[0047] By introducing POSS molecules with a large-scale cage structure and long-chain hydrophobic groups, a microscopic "hydrophobic barrier" was successfully constructed around the hydrolysis-sensitive phosphorus-nitrogen bonds. This barrier effectively blocks the penetration and erosion of water molecules, fundamentally breaking the vicious cycle of "flame retardant hydrolysis producing acid" inducing "matrix autocatalytic degradation," thus endowing the material with excellent long-term resistance to damp heat. Synergistic effect of flame retardancy and mechanical properties: In terms of flame retardancy, the example group achieved the V0 flame retardancy standard while exhibiting a significantly shorter total afterflame time than the comparative group, demonstrating more efficient self-extinguishing ability. This is mainly due to the fact that the POSS cage described in this invention can be transformed in situ into a ceramic skeleton with excellent thermal stability at high temperatures. This skeleton, in synergy with phosphorus and nitrogen elements, promotes a denser and stronger char layer, thereby more effectively isolating heat and oxygen.
[0048] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A moisture-heat resistant and flame-retardant modified polyetheretherketone material, characterized in that, The modified material is prepared from the following parts by weight of raw materials through a melt blending extrusion process: polyetheretherketone: 70-90 parts; Polyphenylene sulfide: 5-15 parts; self-crosslinking modified phosphorus-nitrogen flame retardant: 10-25 parts; hydrolysis-resistant stabilizer: 0.5-2.0 parts; antioxidant: 0.1-0.8 parts; lubricating dispersant: 0.2-1.0 parts; The preparation method of the self-crosslinking modified phosphorus-nitrogen flame retardant is as follows: S1. Dissolve hexachlorocyclotriphosphazene in dry tetrahydrofuran solvent. Under nitrogen protection at 0-5℃, add 1-3% by mass of deionized water to vinyltrimethoxysilane for pre-hydrolysis for 30-60 minutes. Then, add the pre-hydrolyzed vinyltrimethoxysilane dropwise to the above system, and add triethylamine dropwise to convert the generated vinylsilanol into silanolate. The mass ratio of hexachlorocyclotriphosphazene to vinyltrimethoxysilane is 1:1.2-1.5, and the mass of triethylamine added is 0.8-1.0 times the mass of vinyltrimethoxysilane. After the dropwise addition is complete, heat to 40-50℃ and react for 4-6 hours. S2. After the reaction system cools to room temperature, add a hydroxyl-containing cage-like silsesquioxane, the mass of which is 2.0-2.5 times the mass of hexachlorocyclotriphosphazene, and reflux at 65-75℃ for 8-12 hours. S3. After the reaction is complete, the solvent is removed by rotary evaporation. The product is washed with deionized water 3-5 times and dried in a vacuum oven at 80-100℃ to constant weight to obtain a self-crosslinking modified phosphorus-nitrogen flame retardant. The chemical structure of the hydroxyl-containing cage-like silsesquioxane is shown in Formula 1: Formula 1: .
2. The moisture-heat resistant and flame-retardant polyetheretherketone modified material according to claim 1, characterized in that, The hydrolysis-resistant stabilizer is selected from polycarbodiimide.
3. The moisture-heat resistant and flame-retardant polyetheretherketone modified material according to claim 1, characterized in that, The antioxidant is a mixture of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris(2,4-di-tert-butylphenyl)phosphite, with a mass ratio of 1:1-2.
4. The moisture-heat resistant and flame-retardant polyetheretherketone modified material according to claim 1, characterized in that, The lubricating dispersant is one of montan wax, polytetrafluoroethylene micro powder, or calcium stearate.
5. A method for preparing a moisture-heat resistant, flame-retardant polyetheretherketone modified material according to any one of claims 1-4, characterized in that, Includes the following steps: (1) Raw material pretreatment: Polyether ether ketone and polyphenylene sulfide are placed in a forced-air drying oven for high-temperature dehumidification treatment until the moisture content is less than 0.05%; (2) High-speed mixing: The dried polyether ether ketone and polyphenylene sulfide, along with the self-crosslinking modified phosphorus and nitrogen flame retardant, hydrolysis-resistant stabilizer, antioxidant and lubricating dispersant, are put into a high-speed mixer and stirred until the material temperature rises to 110-130℃, then discharged and cooled. (3) Melt extrusion: The mixture is fed into a twin-screw extruder, and after shearing, melting and homogenization, it is extruded; (4) Post-processing: The extruded strips are cooled, dried, granulated and dried to obtain modified material particles.
6. The method for preparing a moisture-heat resistant, flame-retardant polyetheretherketone modified material according to claim 5, characterized in that, The high-temperature dehumidification treatment in step (1) is at a temperature of 120-150℃ and a treatment time of 4-8 hours.
7. The method for preparing a moisture-heat resistant, flame-retardant polyetheretherketone modified material according to claim 5, characterized in that, The temperature settings for each zone of the twin-screw extruder in step (3) are as follows: feeding zone 280-310℃, melting zone 330-360℃, homogenization zone 340-370℃, and die head 330-350℃; the screw speed is controlled at 200-500 rpm.
8. The method for preparing a moisture-heat resistant and flame-retardant polyetheretherketone modified material according to claim 5, characterized in that, In step (3), the screw assembly of the twin-screw extruder includes at least three sets of kneading block elements, and the vacuum degree of the vacuum exhaust section is controlled between -0.08MPa and -0.1MPa.
9. The application of a moisture-heat resistant and flame-retardant polyether ether ketone modified material according to any one of claims 1-4 in the fields of aerospace, electronics and electrical appliances or high-end automobile manufacturing.
Citation Information
Patent Citations
Polyether ether ketone (PEEK) composite material modified from polyhedral oligomeric silsesquioxane (POSS)
CN103146175A